2010
DOI: 10.1093/bioinformatics/btq270
|View full text |Cite
|
Sign up to set email alerts
|

Threshold Average Precision (TAP-k): a measure of retrieval designed for bioinformatics

Abstract: Motivation: Since database retrieval is a fundamental operation, the measurement of retrieval efficacy is critical to progress in bioinformatics. This article points out some issues with current methods of measuring retrieval efficacy and suggests some improvements. In particular, many studies have used the pooled receiver operating characteristic for n irrelevant records (ROCn) score, the area under the ROC curve (AUC) of a ‘pooled’ ROC curve, truncated at n irrelevant records. Unfortunately, the pooled ROCn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…In this study, we utilize the Threshold Average Precision (TAP) [14] method as the evaluation criterion for retrieval efficacy. The TAP method calculates the median Average Precision-Recall with a moderate adjustment for irrelevant sequences just before the threshold.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we utilize the Threshold Average Precision (TAP) [14] method as the evaluation criterion for retrieval efficacy. The TAP method calculates the median Average Precision-Recall with a moderate adjustment for irrelevant sequences just before the threshold.…”
Section: Methodsmentioning
confidence: 99%
“…Usually, the area under the receiver operating characteristic curve (AUC) score is the most popular criterion for the task. However, it was shown that AUC may fail to faithfully reflect the actual quality when the AUC scores are pooled together to evaluate a retrieval system for multiple independent retrieval tasks [16]. AUC is not robust against outlier results.…”
Section: Predicting Top Highly Cited Articlesmentioning
confidence: 99%
“…Finally, AUC does not always decrease as the threshold relaxed to include the entire retrieval list. To address these issues, a new evaluation method called the threshold average precision (TAP-k) was proposed [16]. We will adopt this new method to evaluate the metrics on their performance for predicting top 10% of highly cited articles.…”
Section: Predicting Top Highly Cited Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The implicit assumption is that a curator could use the ranking to decide where to stop looking at the results, therefore a better ranking provides a better user experience. A recently proposed alternative measure of the ranking of the results is the "Threshold Average Precision" (TAP-k) [9], which (in slightly simplified terms) averages precision for the results above a given error threshold. The TAP-k metric is easier to interpret and directly relevant for the end user, who in most cases would not be willing to inspect a long list of results containing many false positives.…”
Section: A Evaluation Measuresmentioning
confidence: 99%